En marge de l’histoire : les fictions médiévales et Gérard Genette - Isabelle Delage-Béland (Perspectives Médiévales)
This paper offers a methodological reflection which brings into dialogue some aspects of Gérard Genette’s thought (fictionality, literariness, paratext, the distinction between “closed” and “open” poetics) in Fiction et Diction (1991), Seuils (1987), and “Vraisemblance et motivation” (1969) and medieval French literature, by examining more precisely the problem of the development of a fictional poetics for fabliaux, short narratives composed from the end of the 12th to the beginning of the 14th century. It aims to provide answers to the two following questions: what can Genette do for the fabliaux and in what ways is the participation of medieval literature in modern critical and theoretical works relevant? We foster the combination of “closed” and “open” poetics described by Genette to use a method which preserves the alterity of medieval fictions such as fabliaux and creates new interpretative paths for these texts that researchers have long wanted to read as documentary sources. Medieval literature thus appears less as a screen on which to project modern theories than as a real interlocutor in the still current discussions on fiction.